Propaganda of LGBT in Qatar’s 2022 FIFA World Cup on Twitter Account - Eva Solina Gultom; Yesti Landepasa (Journal of Humanities Research Sustainability, 2024)
Background. This study sought to examine the contentious methods used by LGBT people to openly disclose their identities on Twitter during Qatar's 2022 FIFA World Cup. Purpose. The objective of this study is to showcase the propaganda of LGBT actions to demonstrate their existence and legitimation during Qatar's 2022 FIFA World Cup from 20 November until 18 December 2022. All data were collected by Twitter account named @Dr_NassMohamed. Method. The researchers implemented the descriptive qualitative research methods through critical discourse analysis on one of the Twitter accounts @Dr_NassMohamed. Results. The outcome demonstrates the numerous attempts made by advocates of the LGBT community to gain social acceptance, as the LGBT community is still viewed as a sexual deviant that is not acknowledged by many nations and faiths. There is negotiation utilizing habitus that they do by using these symbols as capital and using the media through the social media Twitter, so it raises controversy that there are arguments and indoctrinations in the post @Dr_NassMohamed Twitter account based on Human Rights, love is not a crime, and every human being is equal as a form of Bourdieu's capital symbolic to reveal their existence publicly on Twitter. Conclusion. Through the use of human rights framing, the incorporation of LGBT symbols and iconography, interactive engagement with supporters and critics alike, the sharing of personal narratives, and appeals to global solidarity, the Twitter posts served as a form of activism and propaganda to legitimize the existence and rights of the LGBT community. These efforts, inevitably, sparked controversy and backlash, as evidenced by the disagreements, indoctrination attempts, and outright rejection expressed in some of the responses.